Memahami Minat Beli Perawatan Kecantikan melalui Konten Visual Media Sosial: Sebuah Kajian Strategi Pemasaran dan Perilaku Konsumen - Prasetio, Fiona; Teofilus, Teofilus; Tambunan, Damelina Basauli (Jurnal Samudra Ekonomi dan Bisnis, 2025)
A person's interest in purchasing beauty treatments is influenced by different backgrounds, such as economic status and the type of marketing content on social media, each of which can influence perceptions and levels of purchasing interest differently. This study aims to examine the differences in consumer purchasing interest perceptions based on economic status and the type of marketing content on social media. This quantitative study collected data by distributing questionnaires to consumers of a beauty clinic in Surabaya. Data were analyzed using a difference test and Anova two-ways interaction test, using the JASP measuring tool. This study found that purchasing interest in beauty treatments was influenced by the type of marketing content, while the consumer's economic status did not have a significant influence on generating purchasing interest in beauty treatments.